FACTOR ANALYSIS OF COMPETITIVE ACTIVITY INDICATORS OF QUALIFIED HANDBALL GOALKEEPERS (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents the results of a factor analysis of the competitive performance indicators of qualified handball goalkeepers. The study was conducted based on official statistical data from the IHF World Championship 2025. The sample included 10 goalkeepers with the highest efficiency indicators (Save%). The analysis used principal component analysis (PCA) and exploratory factor analysis (EFA). The results allowed us to identify two key factors: the intensity of participation and the quality of goalkeeper actions. Correlation analysis showed that the closest relationship is observed between the number of shots and the total number of saves (r = 0.95), which is a logical confirmation of the interdependence of the workload and the goalkeeper's performance - the more attacks on the goal, the more chances for the goalkeeper to make a save. The average level of correlation between efficiency (%) and the number of saves (r = 0.35). This means that a high number of saves does not always guarantee a high efficiency percentage. Saves/game showed a better correlation with efficiency (r = 0.41) than total saves. This shows the importance of normalizing the data by the number of games. Matches have a relatively weak correlation with efficiency (r = 0.10), which proves that the quality of the goalkeeper's game is more important than the number of matches played. The factor model allowed us to identify two main factors, which determine the goalkeeper's success: component (PC1) summarizes the "volume of work" (number of shots, saves, matches), while the second (PC2) reflects to a greater extent the "quality of actions" (effectiveness of saves).Thus, the conducted study proved the effectiveness of using modern statistical methods (PCA and EFA) for objective analysis of goalkeepers' competitive activities. The obtained results can be used in the practice of sports training, as well as in further scientific works aimed at in-depth study of the specifics of game roles in handball.
Keywords: handball; handball goalkeepers; competitive activity; factor analysis